Potential causes of the preoperative increase in the rectosigmoid cyclic motor pattern: A high‐resolution manometry study. Issue 22 (27th November 2021) - Wells, Cameron I.; Bhat, Sameer; Paskaranandavadivel, Nira; Lin, Anthony Y.; Vather, Ryash; Varghese, Chris; Penfold, James A.; Rowbotham, David; Dinning, Phil G.; Bissett, Ian P.; O'Grady, Greg
Abstract: Background: Cyclic motor patterns (CMPs) are the most common motor pattern in the distal colon. This study used high‐resolution (HR) colonic manometry to quantify trends in distal colonic motor activity before elective colonic surgery, determine the effect of a preoperative carbohydrate load, and compare this with a meal response in healthy controls. Methods: Fiber‐optic HR colonic manometry (36 sensors, 1 cm intervals) was used to investigate distal colonic motor activity in 10 adult patients prior to elective colonic surgery, 6 of whom consumed a preoperative carbohydrate drink (200 kCal). Data were compared with nine healthy volunteers who underwent HR colonic manometry recordings while fasted and following a 700 kCal meal. The primary outcome was the percentage of recording occupied by CMPs, defined as propagating contractions at 2–4 cycles per minute (cpm). Secondary outcomes included amplitude, speed, and distance of propagating motor patterns. Results: The occurrence of CMPs progressively increased in time periods closer to surgery ( p  = 0.001). Consumption of a preoperative drink resulted in significantly increased CMP occurrence ( p  = 0.04) and propagating distance ( p  = 0.04). There were no changes in amplitude or speed of propagating motor patterns during the preoperative period. The increase in activity following a preoperative drink was of similar magnitude to the colonic meal response observed in healthy controls, despite the lesser caloric nutrient load. Conclusion: Distal colonic CMP increased in occurrence prior to surgery, amplified by ingestion of preoperative carbohydrate drinks. We hypothesize that anxiety, which is also known to rise with proximity to surgery, could play a contributing role. Abstract : Distal colonic cyclic motor patterns increased in occurrence prior to surgery, amplified by ingestion of preoperative carbohydrate drinks. We hypothesize that anxiety, which is also known to rise with proximity to surgery, could play a contributing role.